Halfway Homeowners: Eviction and Forced Relocation in a Florida Manufactured Home Park. Issue 2 (18th April 2014) - Sullivan, Esther
<x xml:space="preserve">Abstract</x> The last four decades of US housing policy have seen a shift from the federal allocation of affordable housing as a public good to the neoliberal model of private and for‐profit provision of affordable housing. This shift warrants a study of the link between the interests that now shape low‐income housing markets and the stability of the housing they provide. Nowhere are the effects of this shift more evident than in the homes of the 20 million Americans living in manufactured housing, which is installed largely on the private lands of for‐profit developers who can close mobile home parks and force residents to move themselves and their homes with as little as 30 days' notice. This ethnography of mass eviction in a Florida mobile home park examines state regulations intended to protect residents of closing parks and analyzes how private interests shape the implementation of these policies.